A plastic-damage-contact constitutive model for concrete with smoothed evolution functions. (June 2016) - Jefferson, A.D.; Mihai, I.C.; Tenchev, R.; Alnaas, W.F.; Cole, G.; Lyons, P.
Highlights: A new 3D plastic-damage-contact concrete model is described. Smoothed crack unloading–reloading functions result in efficient robust solutions. The model is validated using plain and reinforced concrete test data. Objectivity is confirmed with respect to both mesh grading and load increment size. Peak loads, failure modes and post-peak responses are all satisfactorily reproduced. Abstract: A new 3D finite element concrete model is described. The model brings together two recently developed sub-models for simulating cracking and crack contact behaviour, both of which use smoothed evolution functions, with a triaxial plasticity model component. A number of examples are presented that validate the model using a range of plain and reinforced concrete test data. These examples demonstrate that the model is numerically robust, has good equilibrium convergence performance and is objective with respect to mesh grading and increment size. The examples also illustrate the model's ability to predict peak loads, failure modes and post-peak responses.